Biomechanical Analysis of the Reasonable Cervical Range of Motion to Prevent Non-Fusion Segmental Degeneration After Single-Level ACDF - Liang, Weishi; Han, Bo; Hai, Yong; Yang, Jincai; Yin, Peng (Frontiers in Bioengineering and Biotechnology, 2022)
The compensatory increase in intervertebral range of motion (ROM) after cervical fusion can increase facet joint force (FJF) and intradiscal pressure (IDP) in non-fusion segments. Guiding the post-ACDF patients’ cervical exercise within a specific ROM (defined as reasonable ROM) to offset the increase in FJF and IDP may help prevent segmental degeneration. This study aimed to determine the reasonable total C0–C7 ROM without an increase in FJF and IDP in non-fusion segments after anterior cervical discectomy and fusion (ACDF). A three-dimensional intact finite element model of C0–C7 was generated healthy cervical conditions. This was modified to the ACDF model by simulating the actual surgery at C5–C6. A 1.0 Nm moment and 73.6 N follower load was applied to the intact model to determine the ROMs. A displacement load was applied to the ACDF model under the same follower load, resulting in a total C0–C7 ROM same to that of the intact model. The reasonable ROMs in the ACDF model were calculated using fitting function. The results indicated that the intervertebral ROM of all non-fusion levels was increased in the ACDF model in all motion directions. The compensatory increase in ROM in adjacent segments (C4/5 and C6/7) was more significant than that in non-adjacent segments, except for C3/4 during lateral bending. The intervertebral FJF and IDP of C0–C7 increased with increasing ROM. The reasonable ROMs in the ACDF model were 42.4°, 52.6°, 28.4°, and 42.25° in flexion, extension, lateral bending, and axial rotation, respectively, with a decreased ROM of 4.4%–7.2%. The postoperative increase in FJF and IDP in non-fusion segments can be canceled out by reducing the intervertebral ROM within the reasonable ROMs. This study provides a new method to estimate the reasonable ROMs after ACDF from a biomechanical perspective, and further clinical studies are needed to confirm this.